PENGARUH PEMBERIAN PAKAN ALAMI DAN PAKAN KOMERSIL TERHADAP PERTUMBUHAN DAN SURVIVAL RATE IKAN JALAI (Channa marulioides) - Nuhman; ivan rahmad, ivan rahmad septiawan; Trisyani, Ninis (FISHERIES Jurnal Perikanan dan Ilmu Kelautan, 2022)
Jalai fish is a freshwater fish that lives in the tropics of India, Indonesia, and the United States. This fish is known as the "emperror snakehead fish", because it has physical characteristics that almost resemble snakes on the head. Fish cultivation has also not been widely carried out by cultivators due to the lack of further research on this fish. Jalai fish has now entered the international market in the field of ornamental fisheries with a fairly high price. Fish growth and survival can be influenced by several factors, including the quality and quantity of feed provided during maintenance. One of the problems that often occur in the cultivation of Jalai Fish (Channa marulioides) is the low growth of seeds. One of the factors causing low seed growth is that the feed given is not in accordance with the needs of the seeds. This study aims to determine the effect of natural feed and commercial feed on the growth and survival rate of Jai fish (Channa marulioides). The research design used in this study was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. Data analysis was carried out with normality test and homogeneity test, then continued with ANOVA (Analysis of Variance) test and to find out between one treatment and another. further test was carried out, namely the Least Significant Difference Test (BNT). The results of this study showed that the percentage of survival was 100%, absolute weight growth was 20.57 grams and the daily growth rate of fish (Channa marulioides) was 2.384%, the best treatment was obtained in treatment P1 (hongkong caterpillar).